Kynurenine pathway metabolites and enzymes involved in redox reactions. (January 2017) - González Esquivel, D.; Ramírez-Ortega, D.; Pineda, B.; Castro, N.; Ríos, C.; Pérez de la Cruz, V.
Abstract: Oxido-reduction reactions are a fundamental part of the life due to support many vital biological processes as cellular respiration and glucose oxidation. In the redox reactions, one substance transfers one or more electrons to another substance. An important electron carrier is the coenzyme NAD +, which is involved in many metabolic pathways. De novo biosynthesis of NAD + is through the kynurenine pathway, the major route of tryptophan catabolism, which is sensitive to redox environment and produces metabolites with redox capacity, able to alter biological functions that are controlled by redox-responsive signaling pathways. Kynurenine pathway metabolites have been implicated in the physiology process and in the physiopathology of many diseases; processes that also share others factors as dysregulation of calcium homeostasis, mitochondrial dysfunction, oxidative stress, inflammation and cell death, which impact the redox environment. This review examines in detail the available evidence in which kynurenine pathway metabolites participate in redox reactions and their effect on cellular redox homeostasis, since the knowledge of the main factors and mechanisms that lead to cell death in many neurodegenative disorders and other pathologies, such as mitochondrial dysfunction, oxidative stress and kynurenines imbalance, will allow to develop therapies using them as targets. This article is part of the Special Issue entitled 'The Kynurenine Pathway in Health and Disease'. Highlights: Kynurenine pathway (KP) is modulated by redox environment. KP metabolites have redox properties. In pathological conditions KP components can contribute to alter redox homeostasis.